Exploring the Innate Human Potential for Positive Adaptation in the Face of Impending Mortality: Is there a Response Shift in Subjective Quality of Life over Time in a Group of Patients with Lung Cancer Receiving Palliative Treatment? - Mannion, Dr. Eileen; Gilmartin, Professor JJ; McInerney, Dr. Veronica; Molony, Ms Kate; Basquille, Ms Emily; Waldron, Prof Dympna (International Journal of Innovative Research in Medical Science, 2020)
Traditionally changes in quality of life (QoL) are assessed using self report questionnaires. They rely on the assumption that the patient’s point of reference does not change over time. However in reality patients with chronic and life threatening illness appear to undergo an adaptation to their disease or “Response Shift” (RS). In this study of a population of patients with advanced lung cancer receiving palliative chemotherapy we examine for a RS in subjective QoL. Methods: 33 patients completed the Schedule for the Evaluation of Individual Quality of Life (SEIQoL), SEIQOL–DW and the EORTC-QLQ C-30 at diagnosis. At 1, 3 and 6 months patients completed SEIQoL/ SEIQOL–DW and retrospectively re-assessed their baseline QoL (the “then” test) using SEIQoL-DW. Results: The initial mean SEIQoL-DW score was 67.48 changing to 66.71 at one month. Retrospectively, patients reassessed their initial mean SEIQoL-DW score as 59.61, suggesting a RS of 7.87 (p ≤0.0001) and an actual improvement in QoL of 7.1 points. At three months the mean SEIQoL-DW score was 65.13; retrospectively patients rated their QoL at one month much lower, mean SEIQoL-DW then – test’ score was 59.92, suggesting a RS of 6.79 (p = 0.0013). At six months patients’ mean SEIQoL-DW score was 61.86. Again, when retrospectively rating their QoL at three months they rated it lower, mean SEIQoL-DW score of 58.84, indicating a ‘positive’ RS of 6.28 (p = 0.0007). Conclusion: Traditional pre/post SEIQOL–DW scores show little change in subjective QOL however by incorporating the ‘then-test’ we can see that patients have undergone a RS and a significant positive change in subjective QOL. By explicitly measuring RS it may be possible to assess changes in QoL with greater validity and sensitivity.